Patterns of maxillofacial fractures treated in a tertiary care government hospital of Puducherry – A descriptive cross-sectional study - Devakumari, Shanmugam; Thanasekar, Vijhayapriya; Biradar, Nandini; Dominic, Neil (Asian Journal of Medical Sciences, 2021)
Background: Maxillofacial trauma is most common in both developing and developed countries. Descriptive studies from various parts of the world helps us in understanding the patterns of these injuries which in turn help in formulating tailor made prevention strategies for that particular geographic region. Aims and Objectives: The aim of this study is to assess the patterns of maxillofacial fractures treated in IGMC & RI in Puducherry from 2011-2018. The objectives are to find out the type of maxillofacial fractures treated, to estimate the demographic data of maxillofacial fracture victims and to assess the treatment modality used (Closed reduction /open reduction and internal fixation (ORIF). Materials and Methods: Data of surgically treated patients of maxillofacial fractures were retrieved, tabulated and analysed using SPSS software – 24 for descriptive and inferential statistics. Results: The estimated results clearly indicate that males were most commonly affected by maxillofacial trauma. The common age group is 20 to 30 years. The major contributing aetiology for trauma is RTA and the common fracture that was encountered was fracture mandible and the fractures were largely managed by open reduction. Conclusion: The results obtained are expected to greatly contribute for the planning of prevention actions and management in health, assistance practices to victims of facial trauma, epidemiological surveillance and road traffic rules.